Negligence Of Public Transport Drivers As a Result Of The Train Accident (Case Study of the Decision of the Medan District Court Class I-A Number 905/Pid.B/2022/PN.Mdn tanggal 28 Juni 2022) - Dengah, Febby Ananda; Elyani, Elyani; Na’im, Khairun (Universitas Pahlawan Tuanku Tambusai, 2024)
Traffic and road transport have a strategic duty to promote national growth and integration as part of initiatives to enhance public welfare, as stipulated by the Republic of Indonesia's 1945 Constitution. In order to support economic growth, the advancement of science and technology, regional autonomy, and state administration accountability, road traffic and transportation which are components of the national transportation system must be developed in all of its potential and roles to ensure safety, welfare, traffic order, and road transportation. The normative juridical method used is a case approach. In research that uses a case approach that needs to be understood, one must understand the legal reasons that the judge uses to make a decision. This study uses qualitative analysis. Logical reasoning, analysis, logic, induction, deduction, analogy, comparison, and so forth are often used in qualitative analysis. The author will discuss the criminal liability of negligent public transportation drivers who cause train accidents in the city of Medan.